Annual Conference with International Participation "Drug Development and Registration: Application of the EAEU GLP Rules" Took Place on December 17, 2021 - article Editorial (Разработка и регистрация лекарственных средств, 2022)
The scientific and practical conference "Drug development and registration: Application of GLP Rules of the EAEU" was held online on December 17, 2021. The conference was organized by LLC "CPHA" and the research and production journal "Drug development and registration". The event was organized with the support of colleagues from Statandocs Academy.